2008
DOI: 10.1523/jneurosci.5539-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Okadaic Acid-Sensitive Protein Phosphatases Constrain Phrenic Long-Term Facilitation after Sustained Hypoxia

Abstract: Phrenic long-term facilitation (pLTF) is a serotonin-dependent form of pattern-sensitive respiratory plasticity induced by intermittent hypoxia (IH), but not sustained hypoxia (SH). The mechanism(s) underlying pLTF pattern sensitivity are unknown. SH and IH may differentially regulate serine/threonine protein phosphatase activity, thereby inhibiting relevant protein phosphatases uniquely during IH and conferring pattern sensitivity to pLTF. We hypothesized that spinal protein phosphatase inhibition would relie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 72 publications
1
71
0
Order By: Relevance
“…Decreases in arterial pH during hypoxia have been reported previously (Golder and Martinez 2008;Iizuka and Fregosi 2007), possibly reflecting an increase in plasma lactate concentration (Romeh and Tannen 1986). Mean arterial blood pressure (MAP) was reduced during hypoxia (P Ͻ 0.01; Table 2) as previously reported (Bavis and Mitchell 2003;Fuller 2005;Wilkerson et al 2008). However, MAP returned to baseline values by 3 min after hypoxia (Table 2).…”
Section: Arterial Blood Gases and Cardiovascular Responsessupporting
confidence: 78%
“…Decreases in arterial pH during hypoxia have been reported previously (Golder and Martinez 2008;Iizuka and Fregosi 2007), possibly reflecting an increase in plasma lactate concentration (Romeh and Tannen 1986). Mean arterial blood pressure (MAP) was reduced during hypoxia (P Ͻ 0.01; Table 2) as previously reported (Bavis and Mitchell 2003;Fuller 2005;Wilkerson et al 2008). However, MAP returned to baseline values by 3 min after hypoxia (Table 2).…”
Section: Arterial Blood Gases and Cardiovascular Responsessupporting
confidence: 78%
“…NADPH oxidase activity is necessary for AIH-induced pLTF (MacFarlane and Mitchell, 2007; MacFarlane and Mitchell, 2008a; MacFarlane and Mitchell, 2009; MacFarlane et al 2009). Since pLTF is constrained by okadaic acid sensitive serine/threonine protein phosphatases (Wilkerson et al 2008), we suggested that NADPH derived ROS inhibit these phosphatases, thereby enabling full pLTF expression. When spinal phosphatases are inhibited with okadaic acid, AIH-induced pLTF is restored in rats pretreated with ROS scavengers (MacFarlane et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…the “Q pathway;” Dale-Nagle et al, 2010) include greater serotonin terminal density, and 5-HT 2A receptor, BDNF, TrkB and phospho-ERK expression. We anticipate interesting changes in the expression of other proteins known to play key roles in AIH-induced respiratory plasticity, such as protein kinase C (Devinney and Mitchell, unpublished), serine/threonine protein phosphatases (Wilkerson et al, 2008) and NADPH oxidase (MacFarlane et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…AIH-induced pLTF is enhanced by prior experience with intermittent hypoxia (Ling et al, 2001; Mitchell et al, 2001; Wilkerson et al, 2008). For example, pretreatment with chronic intermittent hypoxia (CIH) enhances pLTF during anesthesia (Ling et al, 2001) and ventilatory LTF in unanesthetized rats (McGuire et al, 2003).…”
Section: Introductionmentioning
confidence: 99%